Differential treatment response trajectories in individuals with subclinical and clinical PTSD. (March 2016) - Korte, Kristina J.; Allan, Nicholas P.; Gros, Daniel F.; Acierno, Ron
Abstract: Subclinical presentations of posttraumatic stress disorder (PTSD), wherein patients are one or two symptom criteria short of the full disorder, are prevalent and associated with levels of distress and impaired functioning approximating that of full PTSD. Nonetheless, research examining treatment efficacy for this group is in the nascent stage. The purpose of the present study was to examine whether the subclinical PTSD group would: (1) show a greater reduction in PTSD symptoms at pre and post treatment in response to an exposure based treatment and (2) show a greater rate of change over the course of treatment, when compared to the full criteria PTSD group. We also examined whether differences would emerge when examining PTSD symptom clusters. Consistent with predictions, the subclinical PTSD group demonstrated a greater reduction in PTSD symptoms at post-treatment (29%) than those with a PTSD diagnosis (14%). Further, the groups had different treatment trajectories, with the subclinical PTSD group showing a marginally greater rate of change during the course of treatment. Findings also varied by symptom cluster with the subclinical group showing a greater rate of change in the intrusions, hypervigilance, and avoidance symptom clusters. There was not a significant between group difference in the numbing symptom cluster. This study provides preliminary evidence that treating PTSD symptoms at the subclinical level may result in a larger, and more rapid symptom reduction, and thus has implications supporting treatment earlier in the developmental trajectory of the disorder.